Plant ferritin and non-heme iron nutrition in humans - Theil, Elizabeth C.; Briat, Jean-Francois (International Food Policy Research Institute, 2004)
Dietary iron deficiency is the most common and widespread nutritional disorder in the world (DeMaeyer et al. 1985), affecting more than two billion people (WHO 2001). This monograph discusses plant ferritin, an iron-rich, high molecular weight component of legumes that is one of the many dietary non-heme iron sources in human nutrition.